Parental Presence during Induction of Anesthesia and Emergence Delirium Influence the Incidence of Postoperative Maladaptive Behavioral Changes - Gil Mayo, Diego; Sanabria Carretero, Pascual; Gajate Martin, Luis; Alonso Calderón, Jose; Gomez Rojo, Maria; Hernández Oliveros, Francisco (European Journal of Pediatric Surgery, 2023)
Objective Surgical intervention in pediatric patients can cause variable degrees of psychological stress with potential consequences in the perioperative period and even in the long term, after hospital discharge in the form of behavioral changes days and months later. The aim of our study was to determine which preoperative preparation strategy reduces postoperative maladaptive behavioral changes in children undergoing ambulatory pediatric surgery.Materials and Methods This prospective observational study included 638 pediatric American Society of Anesthesiologists physical status I or II patients who underwent ambulatory pediatric surgery. They were grouped into four preoperative preparation groups: not premedicated (NADA), premedicated with midazolam (MDZ), parental presence during induction of anesthesia (PPIA), and parental presence during induction of anesthesia and premedicated with midazolam (PPIA + MDZ). All patients included in the study were contacted by telephone during 1 year posthospital discharge to assess the postoperative maladaptive behavioral changes using the Posthospitalization Behavior Questionnaire (PHBQ). We performed a multivariate analysis to evaluate the influence of type of preparation and behavioral changes.Results Patients in the PPIA and PPIA + MDZ preparation groups presented less postoperative maladaptive behavioral changes compared to patients in the NADA and MDZ groups (odds ratio [OR]: 1.8 [1.1–2.8] and OR 2.2 [1.03–4.49]) during the first week and first month. The intensity of emergence delirium measured by the Pediatric Anesthesia Emergence Delirium (PAED) scale increases the probability of postoperative maladaptive behavioral changes (OR: 1.05 [1.006–1.103]).Conclusion The presence of parents during induction of anesthesia (PPIA and PPIA + MDZ) is a very effective strategy in reducing postoperative behavioral changes. These benefits are more significant in children under 5 years of age.
Keywords: parental presence during induction of anesthesia; emergence delirium; postoperative maladaptive behavioral changes